Pengadaan Perahu Motor Klotok Sebagai Transportasi Pemadam Kebakaran Sungai di Pemukiman Bantaran Sungai di Kelurahan Benua Melayu Laut Kecamatan Pontianak Selatan - Arena, Azza; Sarpawi, Sarpawi; Widhiastuti, Rahayu; Ningsih, Tria (Kapuas, 2022)
Based on the ground figure data, it can be seen that the number of buildings in riverbank settlements has poor spatial planning with a fairly high density, especially in riverbank areas, where many buildings are above the river. Residential houses in the Bantaran Sungai settlement are residential houses that are densely populated and reach access to one residential house and another using old and weathered wooden snaps with several criteria including: residential houses located above the river, residential houses that are not livable. density of residential houses that are difficult to reach in the event of a fire and drowning of residents. community service implementation activities (PPM) Pontianak State Polytechnic 2021 Procurement of klotok motorboats as river firefighting transportation: Boat 4 meters long, 1.5 meters wide, with timbau board wood material, Using 4 cans of oil paint, Fire pump, boat engine.